Pengaruh Manajemen Laba, Kompleksitas Operasi Perusahaan, Solvabilitas, dan Opini Audit Terhadap Audit Delay Pada Perusahaan Sektor Industri Barang Konsumsi di Indonesia Untuk Tahun 2017-2019 - Umi Isnaeni; Yulida Army Nurcahya (Universitas Negeri Surabaya, 2021)
This research purposes to observe the result of Earnings Management, Complexity of Company Operations, Solvency, and Audit Opinions on Audit Delay by the object of research is consumer goods industry sector companies in Indonesia on 2017-2019. This research is include in category of explanatory research which will explain the level of each variable and conduct hypothesis testing to explain the correspondence among the variables in this research. The approachs research is quantitative approach as the data is numbers in the companys financial statements. This research population is Consumer Goods Industry Sector Companies in Indonesia registered on Indonesia Stock Exchange. While, number of samples is 30 corporations in consumer goods industry sector and nominated by purposive sampling technique. The category of data analysis used multiple linear regression analysis using SPSS 23.0 software for windows programs. The existence of substantial result on Audit Delay since the variables of Earnings Management, Complexity of Company Operations, Solvency, and Audit Opinions simultaneously be able to proven in this research. A substantial result is given to Earnings Management on Audit Delay. The Complexity of Company Operations has a substantial positive result on the Audit Delay variable. A substantial negative result is given to Solvency on Audit Delay variable. Meanwhile, Audit Opinions has no substantial result on Audit Delay.